Accessibility and Historical Change: An Emergent Cluster Led Uncles and Aunts to Become Aunts and Uncles - Goldberg, Adele E.; Lee, Crystal (Frontiers in Psychology, 2021)
There are times when a curiously odd relic of language presents us with a thread, which when pulled, reveals deep and general facts about human language. This paper unspools such a case. Prior to 1930, English speakers uniformly preferred male-before-female (M&F) word order for conjoined nouns of relatives, e.g., uncles and aunts; nephews and nieces, rather than the reverse order preferred today for these cases (aunts and uncles, nieces and nephews). This unusual reversal began with mother and daddy and spread throughout half a dozen semantically related binomials over a period of decades. The present work demonstrates that 3 aspects of COGNITIVE ACCESSIBILITY explain why this cluster of binomials reversed their preferred order. We quantify the extent to which the probability of A&B order is predicted by 1) the relative accessibility of the A and B terms individually, 2) competition from B&A order, 3) cluster strength (i.e., similarity to related A’& B’ cases). The current work suggests that the same factors can be used to predict the word order of both familiar and novel binomials generally.